INTEGRATION OF THEORY AND PRACTICE IN PEDAGOGICAL TRAINING: IMPACT ON THE DEVELOPMENT OF KEY COMPETENCIES - Kh. A. Umarov (Web of Journals Publishing, 2025)
The article examines the integration of theoretical and practical components in pedagogical training as the most important factor in the development of key competencies of future teachers. Modern forms and methods of integration are analyzed, such as educational and industrial practice, pedagogical cases, simulations, micro-teaching, project activities, internships and mentoring. Particular attention is paid to assessing the effectiveness of these methods in developing professional skills and reflective abilities. The results of the study confirm that a systematic approach to combining theory and practice helps prepare competitive teachers who are ready to solve professional problems in the conditions of the modern educational space.
Keywords: Teacher training, integration of theory and practice, key competencies, teaching practice, micro-teaching, project work, mentoring, professional development.